THE AFRICAN DREAM IN THE UNITED STATES OF AMERICA(LATE OF 19TH_ EARLY OF21STCENTURY) - SOUALILI, RACHIDA (My University, 2018)
Most of the Africans decided to emigrate, leave their countries of origin, and go to the American Continent. Most of them were looking for freedom, and others were looking for wealth in the new continent, which they believed were abundant. Not all Africans had immigrated to America voluntarily; some of them were in fact taken by force, which were exploited to work in agriculture. The migration of Africans to America was unique in contrast to migratory groups, where most Africans came to North America as servants, trapped in a brutal system of human exploitation. Most of them led a difficult life that last for centuries and they have fought a long battle for freedom, dignity and decent life in the American society. So, this research sheds light on the issue of African-Americans and the way they freed themselves from slavery and the challenge of white rule for centuries until they realized their purpose during the elections of 2008. In my research, I am trying to address many significant events in African-American history from the end of the 19th century, which saw the movement to abolish slavery in the American Continent until the year 2008 that witnessed the realization of the African dream when Obama became president.
“FROM THE WHITE SUPREMACY TO THE BLACK PRESIDENCY”
Keywords: Freedom; African-Americans; African Dream; White Rule; Slavery; Barack Obama